La invención de juegos, en el marco de la creación de problemas de matemáticas - Malaspina Jurado , Uldarico Víctor (2018)
The importance of positive emotions in the teaching and learning of mathematics and the game as a generator of these emotions is highlighted. In this context and within the framework of problem creation, the invention of games that stimulate mathematical thinking is presented. The ludic experiences developed with children and in workshops with teachers in training and in exercise, lead us to conclude that the invention of games, as well as the creation of problems, must be considered in mathematics education as a means and an end. As a means, more oriented towards children, because it stimulates creativity, intuition, mathematical thinking and self-learning; because it favors the stimulation of positive emotions in learning; and because it also generates positive attitudes towards mathematics. As an end, more oriented towards teachers, because it is essential that they develop problem-creation and game-creation skills so that in their classes they can efficiently use these resources with their students.